Effect of Planting Density and K2O:N Ratio on the Yield, External Quality, and Traders' Perceived Shelf Life of Pineapple Fruits in Benin - Djido, Ulrich; Fassinou Hotegni, Nicodeme V.; Lommen, Willemien J. M.; Hounhouigan, Joseph D.; Achigan-Dako, Enoch G.; Struik, Paul C. (Frontiers in Plant Science, 2021)
Pineapple fruit quality, shelf life and yield are important attributes for producers and customers in the pineapple value chains of Benin, where poor quality, short shelf life and low yield are main constraints. We quantified the effects of planting density and K2O: N fertilizer ratio on pineapple yield, external quality and perceived shelf life in four on-farm experiments with cv. Sugarloaf in Benin; two experiments were installed in the long rainy season and two in the short rainy season. A split-plot design was used with planting density as the main factor at three levels: 54,000, 66,600 and 74,000 plants.ha-1. K2O: N ratio was the sub factor with three levels: K2O: N = 0.35 (farmers’ practice), K2O: N = 1 and K2O: N = 2. Results showed that both factors had no effect on crop development variables (such as number of functional leaves and D-leaf length) at flowering induction. Planting density had no effect on total weight per fruit, infructescence weight, total fruit length, infructescence length, crown length, or the fruit shelf life as perceived by traders. Yield increased from 54.9-69.1 t.ha-1 up to 90.1 t.ha-1 with increase in planting density. The yield increase was not at the expense of the fruit weight. Increased K2O: N ratio led to higher fruit weight, whereas fruit length was not affected. The shelf life of fruits produced at a K2O: N ratio of 1 and as perceived by traders was 6 days longer than that of fruits produced at a ratio of 0.35 (farmers’ practice). Based on these results, we suggest to fresh pineapple farmers in Benin to use a combination of 66,600 plants.ha-1 with a K-fertilization scheme based on a K2O:N ratio of 1 to meet both producers’ expectation in terms of fruit yield and customers’ expectations in terms of fruit quality.